Biochemical, Cytological and Microbiological Profile of Cerebrospinal Fluids Analyzed at the Douala General Hospital Laboratory (Global Journal of Medical Research, 2023)
Introduction To investigate whether biochemical cytological and microbiological examinations of CSF could predict infection thus facilitating therapeutic decision-making at the Douala General Hospital laboratory a retrospective cross-sectional and descriptive study was conducted Our study population included the biological records of patients who underwent biochemical cytological and microbiological analysis of cerebrospinal fluid analyzed at the Douala General Hospital laboratory between January 1 2010 and December 31 2016 6years period Method The sampling technique we used was based on the exhaustive consecutive recruitment of all cerebrospinal fluid results analyzed at the Douala General Hospital laboratory that met the inclusion criteria
Keywords: cerebrospinal fluid; biochemistry; cytology; microbiology; laboratory